Les comportements sexuels et le harcèlement sexuel en milieu postsecondaire dans l’Ouest canadien - Delaquis, Stéfan R. (Can J Public Health, 2015)
OBJECTIVES : Risky sexual behaviour associated with sexually transmitted infections (STI) and sexual harassment are important topics in university environments and public health. This article compares these behaviours between student cohorts in 2005 and 2012 from a Western Canadian university. The sexual habits of young adults with multiple partners are also examined. METHODS : Researchers conducted a comparative study of sexual behaviour among approximately 400 students per cohort. Estimates of prevalence and adjusted odds for age group and sex were used to analyze associations between the two cohorts and their sexual behaviours. RESULTS : Trends in sexual behaviour of young adults are maintained with respect to the proportion of those who are sexually active and their number of partners. A reduction in sexual harassment is observed, especially towards women. The condom remains the most frequently used method of contraception, but its use is erratic, particularly among respondents with multiple sexual partners. Drinking and the use of drugs predisposes to unplanned sexual relations and to non-use of means to prevent STIs and pregnancy, particularly among respondents with multiple sexual partners. CONCLUSIONS : The postsecondary student population should be informed of the risks associated with multiple sexual partners and alcohol and drug consumption leading to unplanned sexual acts. A sexual harassment policy contributes to reduction of incidents of harassment within a postsecondary institution.